Correlation of Body Mass Index with Serum Osteocalcin and Insulin-Like Growth Factor Binding Protein-3 in the Assessment of Pubertal Growth Spurt - A Comparative Study - Sengodappan Vaibava Keerthana; Arif Yezdani; Marugulam Sabapathy Kannan; Kesavaram Padmavathy (Indian Journal of Dental Research)
Introduction: Body Mass Index (BMI) percentiles have a bearing on skeletal maturation. The correlation of BMI with serum osteocalcin (OC) and insulin-like growth factor binding protein-3 (IGFBP-3) and cervical vertebral maturation (CVM) assumes even greater importance in orthodontic treatment planning for skeletal Class II jaw discrepancies. The aim of the study was thus to estimate BMI percentiles, serum OC, and IGFBP-3 and correlate it with CVM to assess the opportune pubertal growth spurt. Materials and Methods: Height and body weight were measured to the BMI percentiles of the study participants with skeletal class II malocclusion (n = 51, age 11–18 yrs). Lateral cephalometry was used for CVM staging. Blood was collected to quantitatively assess the serum OC and IGFBP-3 levels using Sandwich-ELISA. Results: Obesity was more common in females compared to males (24% vs. 7.69%) while the reverse was true for underweight (4% vs. 15.39%). The majority of the obese participants belonged to CVM4–CVM6. Mean OC and IGFBP-3 were the highest in the obese category (71.879 ± 5.275 ng/mL, 55.541 ± 5.795 ng/mL). No statistically significant difference was observed in the mean OC and IGFBP-3 levels between males and females (64.993 ± 10.929 ng/mL vs. 58.795 ± 23.054 ng/mL, P = 0.231: 44.030 ± 12.767 ng/mL vs. 48.081 ± 10.843 ng/mL, P = 0.229). Conclusion: The clinical relevance of serum biomarkers (OC, IGFBP-3) and their correlation with BMI percentile and CVM stages could be certainly used to assess the circumpubertal growth status. Obese and severely obese females, though they belong to the age range of 13–17 years and later CVM stages, there was a significant increase in OC and IGFBP-3 serum levels that could be used to plan orthopedic treatment.